(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
We consider the integral equation -L_K^p u = λ f(x,u) + μ g(x,u), with homogeneous Dirichlet condition on a bounded Lipschitz domain of R^N where λ, μ R, p ≥ 2, s ]0,1[, N > ps, f,g : R^N → R are Carathéodory functions with subcritical growth and -L^p denotes a class of operators that includes (-Δ)_p^s, the fractional p-Laplacian. Here μ g represents a small perturbation of λ f. Applying an abstract critical point theorem due to Ricceri, a variational setting developed by Xiang et al. and a Minti-Browder’s theorem, we prove the existence of three weak solutions.